Efficient Solution of Emissivity for the Area Blackbody Based on the Multiple Reflection Method - Xing, Jian; Liu, Dingyu; Cui, Shuanglong (Frontiers in Physics, 2022)
At present, Monte-Carlo method is the only method to evaluate the area blackbody emissivity, so it needs to be compared and verified with other calculation methods. In particular, the efficiency of Monte-Carlo is low when the micro-cavity structure of area blackbody is more complex for higher emissivity. An efficient algorithm for calculating emissivity of area blackbody based on multiple reflection method was put forward in this paper. The multiple reflected light path that radiated into the inner micro-cavity structure of area blackbody was simulated. The ratio of the outgoing light intensity to the incident light intensity was obtained by setting a threshold of the outgoing light intensity, then the area blackbody emissivity was calculated. The simulation results showed that, compared with the Monte-Carlo method, the results of emissivity calculation were similar, and calculation efficiency was increased more than 100 times under the same micro-cavity structure. A practical area blackbody was made based on the simulation results from the proposed multiple reflection method, and the emissivity measurement experiments were carried out and compared to the cavity blackbody at the same temperature. The results showed that the emissivity was near one and stable for NIR (Near Infrared) spectrum range when the temperature was higher than 280℃. Thus, the feasibility of multiple reflection method for calculating the area blackbody emissivity was verified. The multiple reflection method proposed in this paper provided one more design path for developing area blackbodies with more complex micro-cavity structures.